BURNOUT SYNDROME AS A CORRELATE OF JOB SATISFACTION AMONG TEACHERS IN INTERNATIONAL SECONDARY SCHOOLS IN NAIROBI CITY COUNTY, KENYA - Kanja, Joan; Tabitha, Dr. Wang’eri; Cecilia, Dr. Mwangi (IJRDO - Journal of Social Science and Humanities Research, 2022)
Teacher job satisfaction may be determined by various work-related and psychological factors, which could also influence teachers’ performance in their work. The purpose of the study was to investigate the relationship between job burnout syndrome and job satisfaction among secondary school teachers in international secondary schools in Nairobi City County, Kenya. The study was founded on Adams Equity theory and Bandura’s self-efficacy theory. A convergent parallel mixed methods research design was used. Nairobi City County was purposively selected as the study area due to its highest concentration of international secondary schools in Kenya. The target population comprised of all 2078 school teachers, 54 principals and 54 deputy principals working in all 54 international secondary schools in Nairobi City County. A sample of 372 participants comprising of teachers, principals and deputy principals was selected using Yamane formula, factoring in a 10 percent addition to address possible attrition. Quantitative data was collected using closed ended questions adapted from Oldenburg Burnout Inventory, and Job Satisfaction Survey scale. Qualitative data was collected using the tools’ open-ended questions and key informants’ interview guide. The quantitative data were analysed in descriptive statistics and inferential tests using Pearson’s Product Moment correlation. Qualitative data was analyzed in thematic form. The findings indicated that participants with low burnout had the highest job satisfaction mean score M= 68.75, SD= 9.45). The findings also revealed a significant negative relationship between teachers’ burnout and job satisfaction (r(366)= -0.18, P< 0.05). It was recommended that school managers ought to improve the terms of service and prioritize on teachers’ social support systems, with the aim of improving their general wellbeing. Schools’ management should focus on addressing challenges associated with teacher burnout syndrome, including students’ behaviour problems, class sizes, and work environment factors leading to teachers’ emotional exhaustion.